Tapering payments in hospitals Experiences in OECD countries - de Lagasnerie, Grégoire (OECD Health Working Papers, 2015)
This study covers "tapering scale" mechanism in hospital payments, i.e. mechanisms linking unit prices to the volume of services produced. This paper begins with an overview of hospital services and hospital payment methods in OECD countries, focusing more specifically on DRG-based payment. It then reviews studies published on economies of scales in hospitals, which is the economic rationale justifying tapering payments. Thereafter, four case studies from Germany, the US State of Maryland, the Czech Republic and Israel offer a detailed insight into the practicalities of introducing this method of controlling hospital volumes and the impacts it has had